Burst-Like Subcutaneous Electrical Stimulation Induces BDNF-Mediated, Cyclotraxin B-Sensitive Central Sensitization in Rat Spinal Cord - Retamal, Jeffri; Reyes, Andrea; Ramirez, Paulina; Bravo, David; Hernandez, Alejandro; Pelissier, Teresa; Villanueva, Luis; Constandil, Luis (Frontiers in Pharmacology, 2018)
Intrathecal administration of brain derived neurotrophic factor (BDNF) induces long-term potentiation (LTP) and generates long-lasting central sensitization in spinal cord thus mimicking chronic pain, but the relevance of these observations to chronic pain mechanisms is uncertain. Since C-fiber activation by a high-frequency subcutaneous electrical stimulation (SES) protocol causes spinal release of BDNF and induces spinal cord LTP, we propose that application of such protocol would be a sufficient condition for generating long-lasting BDNF-mediated central sensitization. Results showed that application of burst-like SES to rat toes produced (i) rapid induction of hyperalgesia that lasted for more than 3 weeks, (ii) early increase of C-reflex activity followed by increased wind-up scores lasting for more than one week, and (iii) early increase followed by late decrease in BDNF protein levels and phosphorylated TrkB that lasted for more than one week. These changes were prevented by the TrkB antagonist cyclotraxin-B administered shortly before SES, while hyperalgesia was reversed by cyclotraxin-B administered three days after SES. Results suggest that mechanisms underlying central sensitization first involve BDNF release of probably neuronal origin, followed by brief increased expression of likely glial BDNF and pTrkB that could switch early phase sensitization into late one.